Workshop Socio-economic Scenarios for Central America - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
In a workshop from 3 to 5 December in San José, Costa Rica organized by CCAFS and la Universidad para la Cooperación Internacional (UCI), regional stakeholders from governments, development organizations, civil society private sector and academia came together to outline scenarios on future socio-economic drivers of change for food security, environments and livelihoods in the Central American region to be considered together with future climate change. These scenarios can be used to help develop better policies and investments. Photos: E. van de Grift